Penerapan Konsep Desa Literasi Berbasis Kearifan Lokal dalam Meningkatkan Minat Baca Masyarakat di Desa Lembang Lohe Kecamatan Kajang Kabupaten Bulukumba - nasiruddin, fathimah az.zahra; arsyad, susalti nur; ramli, ramli (Universitas Negeri Makassar, 2021)
The purpose of this research is to describe the application of the concept of Literacy Village in increasing the interest in reading the community in Lembang Lohe Village, Kajang District, Bulukumba Regency. This type of research is descriptive qualitative. Collecting data using interviews, observation, and documentation. Data analysis consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study explain that the application of the concept of Literacy Village 1) Literacy activities through counseling on the importance of education, recruitment and upgreading of facilitators, implementing the teaching process of the calistung method based on local wisdom, life skills assistance, routine activity programs for targeted communities and creating a village reading corner are well implemented, 2) 12 competent Facilitators who assist the community in eradicating illiteracy, 3) Catalysts as agents of change, 4) Provision of a Village Incubator, namely a reading corner with a cultural program for at least 5 minutes of reading and forming a smart house with the program 1 hamlet 1 smart house, 5 ) The application of teaching the Calistung method to the community was carried out using the pretest and post-test method, the results of the pretest of 60 selected learning citizens were illiterate, so with the method of facilitating literacy volunteer team facilitators for 2 times a week and continued with family implementing tutors, while the results l Post-test has increased success in recognizing letters, basic reading and arithmetic by up to 85%.